Physical workplaces and human well-being: A mixed-methods study to quantify the effects of materials, windows, and representation on biobehavioral outcomes. (October 2022) - Douglas, Isabella P.; Murnane, Elizabeth L.; Bencharit, Lucy Zhang; Altaf, Basma; Costa, Jean Marcel dos Reis; Yang, Jackie; Ackerson, Meg; Srivastava, Charu; Cooper, Michael; Douglas, Kyle; King, Jennifer; Paredes, Pablo E.; et al.
Abstract: Increasing evidence suggests the built environment can impact occupants' attitudes, behavior, and health. However, few studies have examined these links with large samples in controlled settings. To address this gap, we conducted an experiment ( N = 413) with varied physical features (i.e., materials, windows, and artwork representing diverse identities) to test their effects on biopsychosocial indicators of well-being including belonging, stress, creativity, and pro-environmental concern, measured through physiological sensors and self-reported assessments. Consistent with our hypotheses, participants exposed to natural materials and windows during a stress-inducing task had lower negative stress impacts across various metrics. For certain subgroups, exposure to natural materials also resulted in increased divergent creativity while exposure to windows resulted in increased charitable donations. Finally, participants exposed to diverse representations reported lower stress levels. We discuss the implications of these findings, including methodological challenges surrounding the design, experimentation, and operation of human-centered built environments. Highlights: ● Between-subjects (N = 413) study examining impact of physical workplace on well-being ● Tested eight combinations of two types of materials, windows, and representations ● Belonging, stress, creativity, and environmental concern were measured ● The presence of natural materials and of a window reduced stress in participants ● Trends observed in natural materials improving creativity and diverse icons lowering stress